Increasing the Competence of Village Youth Communities through the Introduction of Cultural Experience and Knowledge in Local Wisdom - Rohtih, Wiwin Ainis; Afifuddin, Mokh. (LPPM Universitas Yudharta Pasuruan, 2023)
Increasing the competence of village youth communities through the introduction of cultural experience and knowledge in local wisdom is a response to the problem of youth who are currently more interested in foreign cultures than their own, which is one of the formation of national character and identity. In addition, youth apathy in local culture, which is strengthened by the onslaught of global Islamic movements or transnational Islam develops among millennials so that religious values that exist in various traditions become misunderstood. This community assistance is located in Ketanen Village, Panceng District, Gresik Regency with the participatory action research method. The mentoring steps include preparation, process, analysis to evaluation. The result of the service is the increasing competence of the youth community, which can be seen by the awareness of the youth community to preserve the cultural heritage that has existed through various positive activities. Through this service, a village history team was formed as a center of information on various local wisdom.